Analysis of lumbar spine loading during walking in patients with chronic low back pain and healthy controls: An OpenSim-Based study - Zhang, Zhuodong; Zou, Jihua; Lu, Pengcheng; Hu, Jinjing; Cai, Yuxin; Xiao, Chongwu; Li, Gege; Zeng, Qing; Zheng, Manxu; Huang, GuoZhi (Frontiers in Bioengineering and Biotechnology, 2024)
Low back pain (LBP) is one of the most prevalent and disabling disease worldwide. However, the specific biomechanical changes due to LBP are still controversial. The purpose of this study was to estimate the lumbar and lower limb kinematics, lumbar moments and loads, muscle forces and activation during walking in healthy adults and LBP. A total of 18 healthy controls and 19 patients with chronic LBP were tested for walking at a comfortable speed. The kinematic and dynamic data of the subjects were collected by 3D motion capture system and force plates respectively, and then the motion simulation was performed by OpenSim. The OpenSim musculoskeletal model was used to calculate lumbar, hip, knee and ankle joint angle variations, lumbar moments and loads, muscle forces and activation of eight major lumbar muscles. In our results, significant lower lumbar axial rotation angle, lumbar flexion/extension and axial rotation moments, as well as the muscle forces of the four muscles and muscle activation of two muscles were found in patients with LBP than those of the healthy controls (p＜0.05). This study may help providing theoretical support for the evaluation and rehabilitation treatment intervention of patients with LBP.